CONVERGENCE OF SCIENCE TECHNIQUES. - Boburjon Xamzayevich bobur; Sabirova Raikhan Shaikhyshevna (Western European Studies, 2024)
The convergence of science techniques represents an interdisciplinary approach where various scientific methods and technologies are integrated to address complex problems. This article explores the concept, its applications, and the implications for future research and innovation.
Keywords: Convergence; Interdisciplinary; Scientific Techniques; Innovation